Protection of Economic Rights Through Royalty Optimization on Film Content in Digital Platforms - Kalbu, Gabrielle Bening; Ramli, Ahmad M.; Ramli, Tasya Safiranita (Fakultas Hukum Universitas Islam Jakarta, 2024)
The emergence of digital platforms based on video-on-demand (VoD) has transformed the distribution and marketing of films from conventional methods to more efficient digital systems that reach wider audiences. However, this transition also presents new challenges, particularly in protecting copyright and related rights, especially regarding the distribution of royalties as part of the creator’s economic rights. This study aims to examine the current legal framework and the urgency of establishing a fair royalty distribution system in the digital film industry. Using a normative juridical method with a descriptive-analytical approach, the study analyzes relevant primary legal sources. The findings show that there is no standardized mechanism for royalty distribution among copyright holders and related rights owners, particularly for works distributed via digital platforms. Royalty agreements are often based on private contracts that vary significantly and lack legal oversight, leaving creators vulnerable to exploitation. The study concludes that a comprehensive and adaptive legal framework is urgently needed. It is recommended that the government and industry stakeholders develop clear, transparent, and equitable digital-based royalty distribution regulations to ensure fair compensation for all rights holders.